Clinical efficacy of customized modular prosthesis in the treatment of femoral shaft metastases - Pu, Feifei; Yu, Yihan; Shao, Zengwu; Wu, Wei; Feng, Jing; Chen, Fengxia; Zhang, Zhicai (Frontiers in Oncology, 2023)
Purpose: To examine clinical outcomes of a specialized modular prosthesis used to fill a bone deficiency following removal of femoral shaft metastases. Methods: Eighteen patients with femoral shaft metastases who underwent en bloc resection and implantation of a personalized modular prosthesis between December 2014 and December 2019 were retrospectively analyzed. Pain, limb function, and quality of life were evaluated using the visual analog scale (VAS), Musculoskeletal Tumor Society (MSTS) scale, International Society of Limb Salvage (ISOLS) scoring system, Karnofsky Performance Status (KPS) scale, and Nottingham Health Profile (NHP) scale. The Kaplan–Meier technique was used to analyze patient survival. Results: The operation duration was 90–150 min (mean, 115 min), and the osteotomy length was 9–16 cm (mean, 11.72 cm). The patients were followed for 12–62 months (mean, 25.28 months). The VAS and NHP ratings were lower at 3, 6, and 12 months after surgery than before surgery, while the MSTS, ISOLS, and KPS scores were higher after surgery than they had been before. These differences were statistically significant (P<0.05). The survival period was between 7 and 62 months (mean, 20.89 months), and the rates of survival at 1-year and 2-year were 72.22% and 27.78%, respectively. Except for two patients with aseptic prosthesis loosening during the follow-up period, there were no problems. Conclusions: En bloc excision and implantation of a personalized modular prosthesis can reduce pain and improve the ability of patients with femoral shaft metastases to perform daily activities, thereby improving their quality of life.